Components of defiance at local level in land conflicts in Mozambique - Pessôa, Marcio (2019)
This paper looks at the emergence of defiance at a local level through an ethnographic description of one of ProSAVANA’s Master Plan hearings in the first half of 2015, and will include the narratives and behaviours of members of civil society organisations, smallholder farmers and Mozambican government agents. It briefly presents features about ProSAVANA, and looks at the public meeting that showed the greatest level of defiance which took place in April 2015, and which makes clearer the contrasts between what the government offered to the peasants, how civil society organisations reacted to this offer, and what the peasants were seeking. The paper provides a better understanding as to what  the real issues are, both main and peripheral, for the subsistence farming communities in ProSAVANA's  framework and how they managed to expose these issues, facing power barriers in the field.